Contrast Agents: Engineering Multifunctional Gold Decorated Dendritic Mesoporous Silica/Tantalum Oxide Nanoparticles for Intraperitoneal Tumor‐Specific Delivery (Part. Part. Syst. Charact. 4/2019). (22nd April 2019) - Kashfi‐Sadabad, Raana; Gonzalez‐Fajardo, Laura; Hargrove, Derek; Ahmadi, Bahar; Munteanu, Daniel; Shahbazmohamadi, Sina; Jay, Michael; Lu, Xiuling
Abstract : In article number1900058, Kashfi and co‐workers develop a radio‐dense nanosystem composed of a tantalum oxide core and a gold decorated dendritic mesoporous silica shell. These nanoparticles specifically target peritoneal metastases, exhibit strong contrast on CT images, and can potentially serve as radiosensitizers for radiotherapy.